Fertility and Modernity - Enrico Spolaore; Romain Wacziarg (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate the determinants of the fertility decline in Europe from 1830 to 1970 using a newly constructed dataset of linguistic distances between European regions. We find that the fertility decline resulted from a gradual diffusion of new fertility behavior from French-speaking regions to the rest of Europe. We observe that societies with higher education, lower infant mortality, higher urbanization, and higher population density had lower levels of fertility during the 19th and early 20th century. However, the fertility decline took place earlier and was initially larger in communities that were culturally closer to the French, while the fertility transition spread only later to societies that were more distant from the cultural frontier. This is consistent with a process of social influence, whereby societies that were linguistically and culturally closer to the French faced lower barriers to the adoption of new social norms and attitudes towards fertility control.
Keywords: J10; J13; N00; N33; 330; fertility control; diffusion; social norms; cultural barriers; demographic transition